2015
DOI: 10.1371/journal.pone.0136047
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Phenotypic Variation and Morphological Divergence of Strains of Folsomia candida (Willem) (Collembola: Isotomidae), the "Standard" Test Springtaill

Abstract: We describe and compare the external morphology of eleven clonal strains and one sexual lineage of the globally distributed Folsomia candida, known as “standard” test Collembola. Of the 18 morphological characters studied, we measured 14 to have significant between-strains genetic variations, 9 of these had high heritabilities (>78%). The quantified morphological polymorphism was used to analyse the within-species relationships between strains by using both a parsimony analysis and a distance tree. These two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…To evaluate the response of F. candida to hypoxia, we measured the mRNA levels of Hc2 (Pick et al, 2009;Xie & Luan, 2014) and other selected putatively stressor oxygen-sensitive genes by quantitative real-time reverse transcription PCR (qRT-PCR). Hc1 (Pick et al, 2009) could not be identified in our culture, which might reflect the considerable differences in F. candida populations (Tully & Potapov, 2015). Pools of 200 adult specimens were exposed to four different hypoxia regimes (see Experimental procedures) along with the appropriate normoxia controls.…”
Section: Hypoxia Response Of F Candidamentioning
confidence: 94%
“…To evaluate the response of F. candida to hypoxia, we measured the mRNA levels of Hc2 (Pick et al, 2009;Xie & Luan, 2014) and other selected putatively stressor oxygen-sensitive genes by quantitative real-time reverse transcription PCR (qRT-PCR). Hc1 (Pick et al, 2009) could not be identified in our culture, which might reflect the considerable differences in F. candida populations (Tully & Potapov, 2015). Pools of 200 adult specimens were exposed to four different hypoxia regimes (see Experimental procedures) along with the appropriate normoxia controls.…”
Section: Hypoxia Response Of F Candidamentioning
confidence: 94%
“…All experimental populations were kept in incubators at 16 °C, with constant humidity (~100%) and in darkness. We raised two genetically distinct clonal strains – labelled TO and HA (Tully et al ., ) – that are known to have different biodemographic strategies under both harsh and good conditions (Tully et al ., ; Tully & Ferrière, ; Tully & Lambert, ) and slight morphological differentiation (Tully & Potapov, ). First, we collected eggs from small cohorts of the two lineages (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…'Cryptic diversity' in F. manolachei Some measure of intraspecific variability was observed in the chaetotaxy of several Folsomia species (e.g. Grow and Christiansen 1976;Wetton 1987;Potapov 2001;Tully and Potapov 2015), F. manolachei included (Deharveng 1982). Thus, a 'manolachei species complex' may potentially involve a larger number of different taxa.…”
Section: Discussionmentioning
confidence: 99%
“…; Tully et al. ; Tully and Ferrière ; Tully and Potapov ). In contrast to large, epedaphic Collembola, genetic and phenotypic plasticity studies have only rarely been conducted in soil‐dwelling species (hemi‐ and euedaphic species).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation